Polskość i europejskość w świadomości młodej prozy polskiej po 1989 roku - Adelgejm, Irina (Postscriptum Polonistyczne, 2020)
The article is an attempt to examine prose of younger generations after 1989 – in the era of globalization and consumption, on the one hand, and in the period when criterion of “Polishness” ceased to be the main way of selfidentification, on the second – in the spatial aspect. The author of the text analyses main psychologicallyartistic types of the experience of space as identity factor.